2008
DOI: 10.1603/0022-0493(2008)101[569:bdicrw]2.0.co;2
|View full text |Cite
|
Sign up to set email alerts
|

Biotypic Diversity in Colorado Russian Wheat Aphid (Hemiptera: Aphididae) Populations

Abstract: The biotypic diversity of the Russian wheat aphid, Diuraphis noxia (Kurdjumov) (Hemiptera: Aphididae), was assessed in five isolates collected in Colorado. Three isolates, RWA 1, RWA 2, and an isolate from Montezuma County, CO, designated RWA 6, were originally collected from cultivated wheat, Triticum aestivum L., and obtained from established colonies at Colorado State University. The fourth isolate, designated RWA 7, was collected from Canada wildrye, Elymus canadensis L., in Baca County, CO. The fifth isol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
15
0

Year Published

2009
2009
2020
2020

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 47 publications
(15 citation statements)
references
References 13 publications
0
15
0
Order By: Relevance
“…At least eight biotypes are present in the United Sates (USA1-8; Burd et al, 2006;Haley et al, 2004;Puterka et al, 2006;Weiland et al, 2008). At least eight biotypes are present in the United Sates (USA1-8; Burd et al, 2006;Haley et al, 2004;Puterka et al, 2006;Weiland et al, 2008).…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…At least eight biotypes are present in the United Sates (USA1-8; Burd et al, 2006;Haley et al, 2004;Puterka et al, 2006;Weiland et al, 2008). At least eight biotypes are present in the United Sates (USA1-8; Burd et al, 2006;Haley et al, 2004;Puterka et al, 2006;Weiland et al, 2008).…”
mentioning
confidence: 99%
“…Additional biotypes have been identified in South Africa, Hungary, Chile, Ethiopia, Argentina, and the Czech Republic that differentially affect resistance in wheat (Basky, 2003;Ricci et al, 2012;Smith et al, 2004). Resistance genes in wheat appear to function in a biotype-specific manner with single genes providing resistance to one or more biotypes (Weiland et al, 2008;Puterka et al, 2007). Resistance genes in wheat appear to function in a biotype-specific manner with single genes providing resistance to one or more biotypes (Weiland et al, 2008;Puterka et al, 2007).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Russian wheat aphids from all over the world as well as from local North American populations were routinely evaluated (Puterka et al 1992, Shufran et al 1997. Recent studies have confirmed the presence of five unique Russian wheat aphid biotypes in Colorado (Haley et al 2004, Weiland et al 2008, two of which were found on noncultivated grasses. This study confirms that while the Russian wheat aphid has undergone many changes as a species, the important grass hosts have not changed.…”
Section: Resultsmentioning
confidence: 99%
“…STARS 9301B, STARS 9577B, STARS 0501B‐0507B, and STARS 0601B‐0643B were resistant to biotypes RWA1 to RWA5 (Puterka et al, 2006). Only germplasm STARS 9301B and STARS 9577B have been tested with RWA6, RWA7, and RWA8, and they were found to be resistant (Weiland et al, 2008). STARS 1006B, STARS 1008B, STARS 1009B, and STARS 1013B have resistance from the same sources as the STARS lines that were found to be resistant to RWA1 to RWA5.…”
mentioning
confidence: 99%